2022
DOI: 10.1186/s12966-022-01312-1
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and mental health in children and adolescents with intellectual disabilities: a meta-analysis using the RE-AIM framework

Abstract: Background Children and adolescents with intellectual disabilities (IDs) tend to have lower levels of physical activity and poorer mental health than their typically developing peers. Studies on the effects of physical activity on the mental health of children with IDs using the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework are scarce. Methods A systematic literature review using six databases (CINAHL, Eric, Psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 70 publications
(181 reference statements)
0
19
0
Order By: Relevance
“…Further research is required to understand better the relationship between ageing, body composition and neuromuscular control of masticatory muscles in PWID. Additionally, studies should explore the potential impact of masticatory muscle training, either alone or combined with physical activity exercise, on overall health and well-being, including cognitive function (Chuhuaicura et al 2019;Lin et al 2020;Kim 2021;Yang et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Further research is required to understand better the relationship between ageing, body composition and neuromuscular control of masticatory muscles in PWID. Additionally, studies should explore the potential impact of masticatory muscle training, either alone or combined with physical activity exercise, on overall health and well-being, including cognitive function (Chuhuaicura et al 2019;Lin et al 2020;Kim 2021;Yang et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The thematic map analysis in the present study identified a few important themes that have been most studied, including physical activities, telemedicine and social support. Physical activities appear to have positive effects on mental health in children and adolescents with ID, but long term effects need to be assessed ( 51 ). Telemedicine can be an effective method of supporting the treatment and rehabilitation of people with ID, though there are risks ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Liang et al detected physical activity–induced benefit for working memory in children and adolescents with ADHD but not in those with ASD . Yang et al found a significant effect size of physical activity interventions for psychological health in children and adolescents with intellectual disability, while nonsignificant effect sizes were examined for internalizing and externalizing problems in those with ADHD . As such, it seems difficult to determine the association of physical activity interventions with mental health when considering NDDs together.…”
Section: Introductionmentioning
confidence: 99%
“…Intensity and intervention sessions (short term vs long term) were found to be moderators between physical activity interventions and executive function in those with ADHD . Meanwhile, physical activity type and time (duration per week) were identified as moderators between physical activity interventions and mental health (including cognitive function and psychological health) in those with intellectual disability, with methodology (eg, study design) and participant characteristics (eg, age) also playing a moderating role …”
Section: Introductionmentioning
confidence: 99%